Aesthetic and ethic between beauty and learning. Different dimensions of the (envious) gaze in educational and knowledge relationships - Emanuela Mancino (Firenze University Press, 2019)
The aesthetic appearance of beauty is intertwined with the experience of looking: and this opens up exciting paths for us to explore within the space of the complex dimensions of learning. The act of "taking something of beauty" (or something related to beauty, including its opposites) is driven by curiosity and desire but accompanied by a sense of fear and paralysis; that which attracts us may become monstruously or terribly beautiful, or - to draw on the lexicon of excess associated with beauty - "too beautiful". There is a sort of unsustainability inherent in beauty. This text explores the dimension of envy, so understood, starting from its ethical declension, bordering with the dimension of justice; in this case, envious glance is rather a questioning look; it wonders, that's to say, how the merit of other's success happened. Envy produces questioning not as about the effects, as about processes. But often the destroying power of the envious glance reaches instead the need of an act of power (a visual one or trough the vision) of the action of other's beauty. It may be the subject of the educational relationship or the subject of learning. These declensions of the envious glance are analysed starting from literature, from myth and from the iconography connected to the power of looking.